Examining the Factors Influencing Poverty Rates in Central Java Province Dist. and City from 2018 to 2023 - Izzah Mariatul Maslakhah; Annisa Nur Rahmawati Utomo; Kartika Supriyaningsih; Yustirania Septiani; Maulia Siti Mukharohmah (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2025)
Poverty is a complex structural problem and is still a major challenge in regional development, especially in Central Java Province which has a high poverty rate nationally. This study aims to analyze the effect of education, unemployment, labor force participation rate (TPAK), and gender inequality on the poverty rate in 35 districts/cities in Central Java Province during the period 2018- 2023. The method used is a descriptive quantitative approach with panel data and Fixed Effect Model (FEM) estimation using Eviews 12 software. The results show that the open unemployment rate variable has a positive and significant effect on poverty. In contrast, the variables of average years of schooling, TPAK, and gender development index show an insignificant effect, although the direction of the relationship is consistent with the theory of development economics. Simultaneously, the four independent variables have a significant effect on poverty with an adjusted R-squared value of 99.46%. This finding confirms the importance of inclusive labor policies and cross-sectoral synergies in sustainable poverty alleviation efforts